TEKANAN ANGGARAN WAKTU SEBAGAI PEMODERASI PENGARUH PROFESIONALISME DAN PENGALAMAN AUDIT PADA KUALITAS AUDIT - Pradipta, Gede Krisna; Budiartha, I Ketut (E-Jurnal Akuntansi, 2016)
This study aims to determine the effect of professionalism on the quality of the audit, the effect of audit experience in audit quality, whether the time budget pressure moderating influence on the professionalism and experience of audit quality audit. This research was conducted at the public accounting firm in the area of ??Bali. Samples in this study of 44 respondents to the sampling technique used was purposive sampling. The data collection method used is the method of questionnaires and documentation. Data analysis technique used is the technique of multiple linear regression analysis. Based on the results of research by distributing questionnaires to 44 respondents, it can be concluded that the professionalism positive and significant impact on audit quality This shows that an auditor has a professional attitude will produce good audit quality. Audit experience but not significant positive effect on audit quality, time and budget pressure as moderating the professionalism and experience of audit, show time budget pressure is not able to moderate.
Keywords: Audit Quality, Professionalism, Experience Of Audit, Time Budget Pressure